2020
DOI: 10.1016/j.devcel.2020.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog Signaling Regulates Epithelial Morphogenesis to Position the Ventral Embryonic Midline

Abstract: Highlights d Convergence of the coelomic epithelium involves cell flattening and disorganization d Hh signaling regulates coelomic epithelium morphogenesis and N-cadherin distribution d Sec5 and RhoU function downstream of Hh d Hh signaling controls dorsal mesentery midline positioning

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 69 publications
1
11
0
Order By: Relevance
“…Knockdown of RhoU expression was described to cause abnormal flattening of the mouse foregut epithelium, with loss of the sub-apical cortical actin domain [ 70 ]. Arraff and colleagues [ 73 ] found that interfering with RhoU activity caused epithelial flattening as well as disruptions in the orientation of coelomic epithelial cells. RhoU has a role also in the FA turnover, in the dismantle of stress fibers and in the formation of filopodia and cell adhesion [ 70 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of RhoU expression was described to cause abnormal flattening of the mouse foregut epithelium, with loss of the sub-apical cortical actin domain [ 70 ]. Arraff and colleagues [ 73 ] found that interfering with RhoU activity caused epithelial flattening as well as disruptions in the orientation of coelomic epithelial cells. RhoU has a role also in the FA turnover, in the dismantle of stress fibers and in the formation of filopodia and cell adhesion [ 70 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Shh signaling has long been recognized to play an important role in controlling positional cell fates in many developing organs, including the limb, the gut, and the spinal cord ( Jessell, 2000 ; Villavicencio et al, 2000 ; McMahon et al, 2003 ; McGlinn and Tabin, 2006 ; Tickle and Towers, 2017 ; Sagner and Briscoe, 2019 ). Although the effects of Shh on cell behavior have received comparatively less attention, Shh has been shown to influence axon guidance ( Zuñiga and Stoeckli, 2017 ), cell migration ( Gordon et al, 2018 ), mesenchymal cell clustering ( Rao-Bhatia et al, 2020 ), and epithelial remodeling in mice, chicks, frogs, and flies ( Corrigall et al, 2007 ; Escudero et al, 2007 ; Nasr et al, 2019 ; Arraf et al, 2020 ). Depending on the context, proteins in the Shh family can have contrasting effects on epithelial cell behavior, promoting apical constriction in the Drosophila eye ( Corrigall et al, 2007 ; Escudero et al, 2007 ), generating short and flat cells in the neural tube ( Fournier-Thibault et al, 2009 and this work), and inducing tall, pseudostratified cells in the chick coelomic cavity ( Arraf et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the effects of Shh on cell behavior have received comparatively less attention, Shh has been shown to influence axon guidance ( Zuñiga and Stoeckli, 2017 ), cell migration ( Gordon et al, 2018 ), mesenchymal cell clustering ( Rao-Bhatia et al, 2020 ), and epithelial remodeling in mice, chicks, frogs, and flies ( Corrigall et al, 2007 ; Escudero et al, 2007 ; Nasr et al, 2019 ; Arraf et al, 2020 ). Depending on the context, proteins in the Shh family can have contrasting effects on epithelial cell behavior, promoting apical constriction in the Drosophila eye ( Corrigall et al, 2007 ; Escudero et al, 2007 ), generating short and flat cells in the neural tube ( Fournier-Thibault et al, 2009 and this work), and inducing tall, pseudostratified cells in the chick coelomic cavity ( Arraf et al, 2020 ). An understanding of the mechanisms by which Shh signaling directs cell morphology will provide insight into how this conserved, positionally encoded molecular mechanism coordinates cell fate with three-dimensional tissue structure.…”
Section: Discussionmentioning
confidence: 99%
“…3K). This indicates that the multilayered mesenchyme undergoes extensive compaction to transform into a two-layered epithelium and raises the possibility that the LPM may undergo a type of convergent extension during MET, wherein the layer converges (thins) in the dorsal-ventral dimension as it extends in medial-lateral and anterior-posterior axes 40 .…”
Section: Resultsmentioning
confidence: 99%
“…The wave-like nature of MET progression is seen particularly clearly when analyzing expression of the cell-cell adhesion protein N-Cadherin (N-Cad; LPM cells express N-Cad and not E-Cad 40 ). In the mesenchymal state (Fig.…”
Section: I White Arrow)mentioning
confidence: 99%